2013
DOI: 10.1089/cap.2013.0059
|View full text |Cite
|
Sign up to set email alerts
|

To Sleep or Not To Sleep: A Systematic Review of the Literature of Pharmacological Treatments of Insomnia in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: This systematic review assessed current evidence on sleep medication for attention-deficit/hyperactivity disorder (ADHD) patients, to establish appropriate guidance for clinicians faced with prescribing such medications. Methods: Five articles (based on four pharmacological compounds) out of a total 337 were identified as evidence to guide pharmacological treatment of ADHD-related sleep disorders. Data regarding participant characteristics, measures of ADHD diagnosis, measures of sleep, and outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
(35 reference statements)
0
28
0
Order By: Relevance
“…Moreover, clonidine seems to be an attractive option targeting insomnia in ADHD [10] and remain a good remedy for paediatric insomnia in general [10] , and a case series has also reported that clonidine seems to be beneficial and fairly well tolerated in intractable sleep disorders in children and young adults with neurodevelopmental disorders [11] .…”
Section: Clonidine In Adhdmentioning
confidence: 99%
“…Moreover, clonidine seems to be an attractive option targeting insomnia in ADHD [10] and remain a good remedy for paediatric insomnia in general [10] , and a case series has also reported that clonidine seems to be beneficial and fairly well tolerated in intractable sleep disorders in children and young adults with neurodevelopmental disorders [11] .…”
Section: Clonidine In Adhdmentioning
confidence: 99%
“…use of electronic gadgets before bedtime), the child's difficulty slowing thoughts and settling for sleep, difficulty for parents setting limits and managing behaviour, psychiatric and medical comorbidities and unwanted effects of stimulant medication may contribute to sleep problems in children with ADHD 12,20…”
Section: About Melatoninmentioning
confidence: 99%
“…Other sleep problems may include resistance in going to bed, night awakenings, difficulty with morning awakenings, daytime sleepiness and restless legs syndrome 9,20. Sleep deprivation potentially worsens ADHD symptoms and intensifies disruptive behaviours 20.…”
Section: About Melatoninmentioning
confidence: 99%
“…The sleep problems reported in children with ADHD include disturbances in sleep quality or quantity, restless leg syndrome (RLS), periodic limb movement (PLM) and sleep disordered breathing (SDB) 4 . Among these the most common problems include difficulty initiating sleep, maintaining sleep (recurrent waking or restless sleep) and early morning awakening with inability to return to sleep [4][5][6][7] . There is a relationship between sleep and ADHD symptoms, which seem to overlap with very little separation.…”
Section: Introductionmentioning
confidence: 99%
“…However there are no approved treatments, either prescribed or over-the-counter preparations for managing sleep disturbances such as behavioural insomnia in these children, as compared to those in general paediatric populations 4,26,27 . Despite the widespread use of these unapproved agents to aid sleep in children with ADHD, few data exist on their safety, tolerability and efficacy.…”
mentioning
confidence: 99%